A coumarin dimer probe of mechanochemical scission efficiency in the sonochemical activation of chain-centered mechanophore polymers1. Issue 44 (4th June 2015) - Kean, Zachary S.; Gossweiler, Gregory R.; Kouznetsova, Tatiana B.; Hewage, Gihan B.; Craig, Stephen L.
<x xml:space="preserve">Abstract</x> A coumarin dimer mechanophore is used to probe the effect of polymer size and polydispersity on mechanochemical activation.